1996
DOI: 10.1128/jb.178.3.922-926.1996
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the Anabaena sp. strain PCC 7120 ntcA gene: multiple transcripts and NtcA binding

Abstract: The Anabaena sp. strain PCC 7120 ntcA gene showed multiple transcripts with different 5 ends. The relative abundance of transcripts varied in response to nitrogen availability. The ntcA product, NtcA, showed binding to the promoter region of its own gene. The binding site mapped to a region between the transcription start site used under nitrogen-replete conditions and the start sites used under nitrogen-limiting conditions, suggesting that NtcA regulates its own expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 22 publications
2
84
0
Order By: Relevance
“…The ntcA expression pattern with high transcript levels in the presence of ammonium as presented here for Trichodesmium is also encountered in the N 2 fixers Cyanothece and Anabaena (Ramasubramanian et al, 1996;Bradley and Reddy, 1997). The latter produces three different transcripts, two of which seem to originate from an atypical promoter that involves NtcA binding (Ramasubramanian et al, 1996). Thus, ntcA may be involved in the development of nitrate utilization as its expression is high both in nitrate-grown Trichodesmium IMS101 (this study) and in Cyanothece BH68K (Bradley and Reddy, 1997).…”
Section: Transcriptional Regulationmentioning
confidence: 81%
See 2 more Smart Citations
“…The ntcA expression pattern with high transcript levels in the presence of ammonium as presented here for Trichodesmium is also encountered in the N 2 fixers Cyanothece and Anabaena (Ramasubramanian et al, 1996;Bradley and Reddy, 1997). The latter produces three different transcripts, two of which seem to originate from an atypical promoter that involves NtcA binding (Ramasubramanian et al, 1996). Thus, ntcA may be involved in the development of nitrate utilization as its expression is high both in nitrate-grown Trichodesmium IMS101 (this study) and in Cyanothece BH68K (Bradley and Reddy, 1997).…”
Section: Transcriptional Regulationmentioning
confidence: 81%
“…and thus yields two transcript populations, the latter one regulated by NtcA (Luque et al, 1994;Lindell et al, 1998). The ntcA expression pattern with high transcript levels in the presence of ammonium as presented here for Trichodesmium is also encountered in the N 2 fixers Cyanothece and Anabaena (Ramasubramanian et al, 1996;Bradley and Reddy, 1997). The latter produces three different transcripts, two of which seem to originate from an atypical promoter that involves NtcA binding (Ramasubramanian et al, 1996).…”
Section: Transcriptional Regulationmentioning
confidence: 90%
See 1 more Smart Citation
“…Any remaining traces of oxygen, and any that diffuses into the cell along with N # , are removed by several mechanisms, the most important of which is probably respiration. Because they lack Rubisco, heterocysts do not fix Wei et al, 1993Ramasubramanian et al, 1994Ramasubramanian et al, , 1996Jiang et al, 1997 In row H (homology), ' None ' indicates that no homology has been found to any known proteins in the databases. Abbreviations : MCH, multiple contiguous heterocysts ; MCP, multiple contiguous heterocysts ; ND, not determined.…”
Section: Function and Metabolismmentioning
confidence: 99%
“…1). It has been demonstrated in PCC 7942 and PCC 7120 that NtcA binds to the promoter region of and activates genes involved in nitrogen control such as glnA, nir, and ntcA itself (3,9,12,13). Given its similarity to the NtcA proteins from PCC 7942 and PCC 7120, it is possible that the Cyanothece NtcA protein may bind similar target sequences.…”
mentioning
confidence: 99%